Effects of Stigma on the Relationship Between Perceived Social Support and Sexual Satisfaction Among Breast Cancer Survivors. Issue 6 (25th April 2022) - Zhang, Yuxin; Zhao, Jie; Jiang, Nan; Wang, Ting; Cao, He; Wang, Quqing; Wei, Xiaomin; Wang, Jiwei; Yu, Jinming
ABSTRACT: Background: Sexual satisfaction is one of the issues faced by breast cancer survivors (BCSs). Aim: This study aims to explore the mediation of stigma in the relationship between perceived social support (PSS) and sexual satisfaction among breast cancer survivors. Methods: A cross-sectional study was conducted among 918 BCSs in Shanghai Cancer Rehabilitation Club. Data were collected using an online questionnaire including questions on sociodemographic characteristics, health status, PSS, stigma and sexual satisfaction of participants. The bootstrap method was used to test the significance of the simple mediation model. Outcomes: The simple mediation of stigma was found significant in the relationship between PSS and sexual satisfaction. Results: Stigma plays an intermediary role in the relationship between 2 dimensions of PSS (family and friends) and sexual satisfaction, but not in the relationship between the dimension of other significant people of PSS and sexual satisfaction. Clinical Translation: It is important to reduce stigma when improving the sexual satisfaction of BCSs from the perspective of PSS. Strengths & Limitations: The mediating role of stigma in the relationship between PSS and sexual satisfaction among BCSs has been shown for the first time. Study limitations include limitations in the representativeness of population by the study sample and the cross-sectional study design. Conclusions: Stigma mediates the relationship between PSS and sexual satisfaction, which needs to be eliminated in intervention practice.